2000
DOI: 10.1002/1096-9071(200101)63:1<45::aid-jmv1006>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6 infection in neoplastic and normal brain tissue

Abstract: The presence and variant distribution of human herpesvirus 6 (HHV-6) was investigated by a nested polymerase chain reaction (PCR) in 118 biopsies from patients affected by nervous tissue tumor (115 primary tumors and 3 metastasis) and in 31 autopsy samples from the brain of healthy individuals. HHV-6 DNA sequences were detected in normal and neoplastic nervous tissue at a frequency of 32% and 37%, respectively. In both tissues, variant A was three times more frequent than the variant B. Peripheral blood lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 42 publications
1
56
1
1
Order By: Relevance
“…An extensive study on a large cohort of children and adults documented a relative predominance of HHV-6A in cerebral spinal fluid from children. Those authors claimed that this was suggestive of a greater neurotropic potential of HHV-6A (19) and is in agreement with the detection of HHV-6A in autopsy brain material three times more frequently than HHV-6B (9). The results in this study are strongly supportive for a variant-specific tropism and infection pattern for HHV-6 in HPDA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An extensive study on a large cohort of children and adults documented a relative predominance of HHV-6A in cerebral spinal fluid from children. Those authors claimed that this was suggestive of a greater neurotropic potential of HHV-6A (19) and is in agreement with the detection of HHV-6A in autopsy brain material three times more frequently than HHV-6B (9). The results in this study are strongly supportive for a variant-specific tropism and infection pattern for HHV-6 in HPDA.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, HHV-6 has also been demonstrated to be the causative agent of encephalitis in adult immunosuppressed patients such as bone marrow transplant recipients (40). These findings, possibly due to local viral reactivation, would suggest that not only does HHV-6 spread to the central nervous system (CNS), but it can also establish latency in the CNS, as confirmed by the detection of HHV-6 DNA in autopsy samples from healthy individuals (9).…”
mentioning
confidence: 96%
“…19 In brief, after hydration and rinsing, slides were blocked in a 10% horse serum (Gibco Invitrogen Corp.)/phosphate-buffered saline (PBS) solution and then incubated overnight at 4 °C with a 2% horse serum/PBS solution containing anti-HHV-6 gp116/54/64 mouse monoclonal antibody that reacts with both HHV-6A and B variants (1:50) (Advanced Biotechnologies). 31 IHC reactivity was detected using a DAKO LSAB 2 System (DAKO Corp., Carpinteria, CA) following the manufacturer's instructions with a 10-minute counterstain in Mayer's hematoxylin (Fluka Chemie, Steinheim, Germany).…”
Section: In Situ Immunohistochemistrymentioning
confidence: 99%
“…15 Although the role of HHV-6 in human CNS disease remains to be fully defined, a number of studies have suggested that the CNS can be a site for persistent HHV-6 infection. 16,17 Autopsy material from a wide variety of normal 18 and diseased 19,20 brains has documented HHV-6 infection in the CNS, although its role as a causative agent is unclear. Cell types reported to be infected include oligodendrocytes, astrocytes, and possibly neurons.…”
mentioning
confidence: 99%
“…The detection of fingerprints of these two ubiquitous viruses known to be latent in blood B-(EBV) or T-(HHV-6) cells is intriguing, since the primary encounter with either virus usually occurs before or during puberty, the same time that epidemiologic evidence indicates exposure to the disease-causing agent of MS. However, HHV-6 is found not only in brain and CSF of MS patients, but also in neoplastic and normal brain (93), suggesting that the detection of virus reflects its reactivation from latency and/or blood T-cells trafficking through brain. Other reports do not support an association between HHV-6 and MS. One study found serum IgM responses to HHV-6 in only 1 of 55 MS patients, and IgG responses in 15 of the patients (94).…”
Section: 31mentioning
confidence: 99%